SURVEI PERAN NILAI-NILAI OLIMPISME PADA MASYARAKAT DI KABUPATEN KARAWANG TAHUN 2019 - Afrinaldi, Rolly; Gemael, Qorry Armen; Nugroho, Setio; Prasetyo, Tommy Rizki (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2020)
This study aims to determine the role of social values in society in Karawang Regency in 2019. This study uses a quantitative approach with descriptive survey research type. This type of descriptive survey research relates to situations that require certain data collection techniques, such as: interviews, questionnaires, or observations. This research was carried out in Karawang regency with an implementation plan in May 2019. This research variable is the role of Olympic values. Variable olimpism values are the results of the evaluation of Olympic values, namely: Excellence, Respect, and Friendship. The sample used in this study was 60 people in Karawang Regency. Data collection techniques using a questionnaire. Furthermore, the data obtained were analyzed using descriptive analysis of percentages with the help of a computer through the SPSS 20.00 program. The results showed the role of Olympic values in society in Karawang Regency in 2019 obtained 69% of the values of Olympism have a role in society and 31% of the values of Olympism have no role in society.